PHOTOSENSITIVE EPILEPSY, OCCIPITAL AND FRONTAL CORTEX - V. A. Karlov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: this article discusses the unique features of the structural-functional organization of the visual distance perception which in contrast to other distant sensory systems has not only afferent but also efferent part – the frontal visual field and, smooth and stripy muscles of the eye which accordingly service of the visual function. The article shows the increasing importance of the efferent part of the visual system in the present conditions of real and virtual movements of visual objects. The case of photosensitivity in epilepsy proves the fact that the efferent part of the visual system can react in a protective way to the rhythmic photo-stimulation.